5′-CpG island methylation of theLKB1/STK11 promoter and allelic loss at chromosome 19p13.3 in sporadic colorectal cancer. Issue 2 (1st August 2000) - Trojan, J; Brieger, A; Raedle, J; Esteller, M; Zeuzem, S
Abstract : BACKGROUND: In patients with Peutz-Jeghers syndrome (PJS), causative germline mutations in the LKB1/STK11 gene on chromosome 19p13.3 have been identified. Because of the loss of heterozygosity (LOH) at 19p13.3 in hamartomas and the cancer susceptibility of patients with PJS, LKB1/STK11 is suggested to act as a tumour suppressor. However, the frequency of genetic and epigenetic inactivation of LKB1/STK11 in sporadic tumours is unclear. AIMS: To investigate the LKB1/STK11 gene for promoter hypermethylation and allelic loss in tumour specimens of patients with sporadic colorectal cancer. METHODS: DNA from 50 consecutive paraffin embedded sporadic colorectal adenocarcinomas and corresponding normal epithelium was extracted. After bisulphite treatment, specimens were analysed for methylation of the LKB1/STK11 promoter 5′-CpG island by methylation specific polymerase chain reaction (MSP). In addition, tumours were analysed for LOH of chromosome 19p13.3. In tumours exhibiting LOH, LKB1/STK11 was sequenced. RESULTS: MSP was successful in 48 of 50 tumour specimens. Of those, four (8%) demonstrated hypermethylation of the LKB1/STK11 promoter 5′-CpG island. Moreover, LOH at either D19S886 or D19S878 was observed in five of 38 (13%) informative tumours. All five tumours showing LOH at 19p13.3 were advanced and four of five were located in the left sided colon. There was no correlation between LOH and LKB1/STK11 promoter hypermethylation or somatic mutation. CONCLUSIONS: In sporadic colorectal cancer, hypermethylation of the LKB1/STK11 promoter and allelic loss at the STK 11 gene locus are rare events. LOH at 19p13.3 was associated with advanced tumour stage and left sided location but not with LKB1/STK11 promoter hypermethylation or somatic mutation.